A contribution to the knowledge of fly fauna in the Kingdom of Saudi Arabia: new country records and an account of flies identified from Rawdhats, Riyadh Region, with biogeographical remarks (Insecta: Diptera). Issue 21 (11th June 2018) - El-Hawagry, Magdi S.; Abdel-Dayem, Mahmoud S.; Al Dhafer, Hathal M.
ABSTRACT: A total of 80 fly species (Insecta: Diptera) belonging to 66 genera, and representing 26 families was identified from three natural areas or 'Rawdhats' in the Riyadh Region of the Kingdom of Saudi Arabia (KSA). The Rawdhats surveyed are Al-Harmaliyah (Al Quwayiyah Province), Al-Sabalah (Azulfi Province) and Farshet Sheaal (Al Aflaj Province). One family, one subfamily, 11 genera and 18 species were recorded for the first time from KSA, namely: the family Trixoscelididae; the subfamily Suilliinae (Heleomyzidae); the genera Oligodranes (Bombyliidae), Pseudomphrale (Scenopinidae), Actorthia (Therevidae), Crossopalpus (Hybotidae), Scatella (Ephydridae), Suillia (Heleomyzidae), Trixoscelis (Trixoscelididae), Renocera [Sciomyzidae], Melanophora and Stevenia [Rhinophoridae], Miltogramma [Sarcophagidae]; and the species Eremisca heleni (Efflatoun) and Ommatius tenellus van der Wulp [Asilidae], Oligodranes sp. [Bombyliidae], Pseudomphrale flavoscutellata Kröber [Scenopinidae], Actorthia lacteipennis (Becker), Actorthia sp. and Efflatouniella sinatica Mohammad and Badrawy [Therevidae], Crossopalpus hirsutipes Collin [Hybotidae], Eumerus mucidus Bezzi [Syrphidae], Ephydra riparia Fallén and Scatella sp.[ Ephydridae], Suillia apicalis (Loew) [Heleomyzidae], Trixoscelis sp. (Trixoscelididae) and Renocera pallida (Fallén) [Sciomyzidae], Goniurellia longicauda Freidberg [Tephritidae], Melanophora sp. and Stevenia sp. [Rhinophoridae], and Miltogramma sp. [Sarcophagidae]. The zoogeographic affinities of the identified species showed a closer affiliation with the Palaearctic Region (26%) than to the Afrotropical Region (12.5%), while about 16% of the species were of both Afrotropical and Palaearctic affinities. Elements from other regions were apparently absent. The result support the idea that the central Arabian Desert which includes our study area is a transitional zone between the Palaearctic and Afrotropical regions.